Seasonal Pattern in the Relapses of Crohn's Disease and Ulcerative Colitis in British Columbia - Frank H Anderson; Lecheng Zeng (Canadian Journal of Gastroenterology)
Ulcerative colitis (UC) reportedly has a seasonal variation of exacerbations. No seasonal variation of relapses in Crohn's disease (CD) has been reported. A retrospective study of the monthly distribution in the relapses of inflammatory bowel disease (IBD) demonstrated seasonality in both UC and CD. From 1971-93, 226 patients (CD=139, UC=87) with regular follow-ups for at least 13 consecutive months were analyzed. In the study period, 592 relapses occurred in CD patients and 300 in UC patients. The peak relapse seasons were autumn and winter and the lowest was summer, for both CD and UC. The seasonal pattern was independent of sex. These results support the view that seasonal factors may be involved in the relapse of IBD.